Differentiation And Positioning Of Islamic Boarding School: Internalization Of Special Values As A Unique Selling Proposition (Usp) - Siti Nur Aviatun Hasanah; Rifka Jannatul Firdausiyah; Moh. Kamil; Ittaqillah haitsuma kunta; Muhammad Durrin Ni'am; Moh. Rofik; Abdullah Abdullah (Educazione: Journal of Education and Learning, 2025)
This study aims to analyze the differentiation and positioning of Islamic boarding schools (pesantren) through the internalization of distinctive values ​​as a Unique Selling Proposition (USP) to enhance the competitiveness of educational institutions. The method used was a qualitative approach with a case study design, through in-depth interviews, participant observation, and documentation analysis of leaders, teachers, and students. The results indicate that the differentiation of Islamic boarding schools lies in the strength of distinctive values ​​internalized in the organizational culture, such as spirituality, discipline, and integrity. These values ​​serve as USPs that shape the institution's image and increase public trust. Furthermore, transformational leadership contributes to knowledge management, engagement strategies, and confidence building among Islamic boarding school residents, thus creating a healthy competitive culture. The implications of this study emphasize that the internalization of distinctive values ​​must be strategically integrated into institutional management as a competitive advantage. This is crucial for strengthening the positioning of Islamic boarding schools amidst increasingly dynamic educational competition.